(untitled) (Research, Society and Development, 2021)
Objective: To present the indices of vitamin D alterations in patients in the city of Goiânia, Goiás. Methodology: In order to carry out this work, a data survey was carried out from patients at the Hospital do Policial Militar do Estado de Goiás, in Goiânia-Go. Data analysis was performed using Microsoft Excel O. Data were then analyzed using GraphPadPrism software. After the results were tabulated and the analyzes carried out, tables with vitamin D values in the analyzed population were constructed. Analyzes were filtered from the initial sample of 523 patients, divided by gender, age and vitamin D levels. Results: There was a greater number of patients with high doses of vitamin D, when compared to the number of patients with doses normal or below the reference value. Conclusion: It was concluded that people are increasingly distant from sources of vitamin D, and with this, the health of the population is being harmed, especially women.